2012
DOI: 10.1037/a0028132
|View full text |Cite
|
Sign up to set email alerts
|

Generalized anxiety disorder: A comparison of symptom change in adults receiving cognitive-behavioral therapy or applied relaxation.

Abstract: These findings allowed us to identify differences in a mechanism of change in GAD symptoms during 2 treatments and to provide some support for the idea that similarly efficacious treatments may produce symptom change via different mechanisms in a manner that is consistent with the theoretical rationales on which the treatments are based.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
4
25
0
6
Order By: Relevance
“…The finding that improvement in RNT was strongly linked with subsequent decreases in depression and anxiety builds on previous work indicating that changes in rumination and/or worry (pre-to mid-treatment) are associated with later changes in symptoms (e.g., Donegan & Dugas, 2012;Van Aalderen et al, 2012). The design of the current study provides even stronger evidence than earlier work for the role of RNT in symptom improvement, as we were able to establish the temporal precedence of RNT relative to changes in depression and anxiety and also controlling for potentially confounding influences.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The finding that improvement in RNT was strongly linked with subsequent decreases in depression and anxiety builds on previous work indicating that changes in rumination and/or worry (pre-to mid-treatment) are associated with later changes in symptoms (e.g., Donegan & Dugas, 2012;Van Aalderen et al, 2012). The design of the current study provides even stronger evidence than earlier work for the role of RNT in symptom improvement, as we were able to establish the temporal precedence of RNT relative to changes in depression and anxiety and also controlling for potentially confounding influences.…”
Section: Discussionsupporting
confidence: 64%
“…Two studies of mindfulness-based treatment for depression also found that decreased levels of worry and rumination (change scores) mediated the effect of treatment on depression outcome (Van Aalderen et al, 2012). Similarly, changes in worry (measured daily) have been shown to partially mediate the effect of time on decreased anxiety in CBT and applied relaxation for GAD (Donegan & Dugas, 2012).…”
mentioning
confidence: 95%
“…We subsequently tested a reverse mediation model, where changes in worry predicted changes in IU over time. Repeated assessments allowed us to include the mediator as a “lagged“ variable with temporal precedence; that is, we examined whether changes in the mediator at time point t influenced the outcome variable at time point t + 1 (see for example Aderka, Foa, Applebaum, Shafran, & Gilboa-Schechtman, 2011; Donegan & Dugas, 2012). For each model we also indexed the significance of potential mediated effects using the Prodclin program (MacKinnon et al, 2007), which provides confidence intervals for the indirect effect, and calculated the percent mediation for each model using the procedures described by Kenny and colleagues (2003).…”
Section: Methodsmentioning
confidence: 99%
“…More precisely, a number of studies have investigated the potential for internet-delivered treatments for GAD and they have reported significant post-treatment and follow-up gains [33,48-51] similar to those found in face-to-face treatment studies [52]. A recent meta-analysis of internet-delivered treatments for GAD demonstrated large post-treatment effects for GAD symptoms ( d  = 0.91) and pathological worry ( d  = 0.73) in favor of the active interventions when compared to waiting list control groups [53].…”
Section: Introductionmentioning
confidence: 94%